Goldsmith, Michael (London, 2011)
2011 "Goldsmith, Michael", 2011, HistoryTalk Michael was born in Cork in Ireland and came to live in Ladbroke Grove, London, as a 9 year old boy with his family in 1953. Michael's first job was as a trainee TV and radio engineer at Bush Radio in Chiswick, but after a short while he entered the office there as a trainee cost accountant. Both of these jobs were short-term. Still a teenager, Michael took advantage of a scheme to emigrate to Australia. Having briefly taken a couple of jobs there, he joined the Australian army, seeing active service in Vietnam. In 1967, Michael came back to live in London, initially obtaining employment as a labourer at Richey's hairdresser in Mayfair, before undertaking a government training scheme which qualified him as a heating and ventilation fitter. He obtained employment in this field at a firm called Benham's as a fitter/fabricator, and he also went on to develop skills as a welder, which stood him in good stead in his subsequent employment with George Wimpey and Guinness, and at various on-site jobs. He later went on to set up his own welding business in partnership with a friend. At this point, Michael had begun volunteering for various organisations such as The Samaritans and a hospice, and decided on a complete career change, utilising his caring nature by gaining employment as a residential social worker with young adults with learning difficulties. Thereafter, Michael worked as a Residential social worker with older people, and from there went on to work for the Autistic Society. Michael regards this career change as the most fulfilling part of his life, and continues to actively participate in local community activities.